Pelindungan Hukum Atas Perbuatan Adaptasi Naskah Yang Dilakukan Oleh Sutradara Dalam Pertunjukan Teater - Ahmad Muhsin (Universitas Islam Indonesia, 2020)
This study aims to analyze the protection of copyright law in Indonesia. The object of the study is a theater script adapted by the director in a theater performance in Yogyakarta. The formulation of the problem posed in this research is, how is the legal protection for the copyright of theater scripts that are adapted by the director in theater performances according to the Copyright Law? This study applies normative method that uses statutory and conceptual approach. The result of the study concludes that theater scriptwriters should have legal protection for their scripts that are adapted into theater performances. There are a number of factors that influence the legal protection of a written text adapted into a theater performance, namely the legal regulations, law enforcement factors, and cultural factors.